A Suggested Model for Studying Technopreneurial Intention in Malaysia - Koe, W-L; Ezaili Alias, N; Ismail, S; Halim Mahphoth, M (KnE Social Sciences, 2018)
Technology entrepreneurship or technopreneurship is a future trend in the era of industrial revolution 4.0 (IR 4.0). Technopreneurship requires innovative, young and information-communication technology (ICT) savvy individuals. Many countries around the world, including Malaysia, has put in a lot of efforts to develop entrepreneurial skills among youngsters especially the students. However, developing competitive young technopreneurs remains challenging in Malaysia. For instance, Malaysians scored low in several entrepreneurial behaviors and attitudes identified by Global Entrepreneurial Monitor (GEM). Furthermore, not many Malaysians have started new businesses and the country recorded a low and declining early-stage entrepreneurship rate. Moreover, university students were not showing great interest in becoming entrepeneurs during thier tertiary eduation. The future of IR 4.0 is unpredictable and full of challenges. Thus, the unattended issue of developing young and competitive technopreneurs will affect the ways Malaysians confront the unknown future. In the entrepreneurship literature, technological capability aspects and psychological aspects such as entrepreneurial orientaion (EO) and entrepreneurial intention are under-researched. Therefore, based on Bandura’s self-efficacy theory and individual EO (IEO) concept, this study proposes a model to explain the direct and indirect influence of ICT self-efficacy and IEO on technopreneurial intention. The potential contribution of this study is two-fold. Literally, it develops a new model for investigating technopreneurial intention. Practically, it provides insights on the implementation of policies in developing competitive entrepreneurial graduates, creating technology innovative individuals and transforming Malaysia into a knowledge economy. It also identifies the types of ICT capabilities that are crucial in developing innovative and entrepreneurial human capital. Additionally, it helps to strengthen and increase the particiaption of youngsters in the economy through technology entrepreneurial activities. Keywords: entrepreneurial intention, model, students, technology